Closed Reduction Percutaneous Pinning Compared with Open Reduction Internal Fixation in Treating Supracondylar Fractures: A Systematic Review - I Made Yedi Wisnawan; I Kadek Yoga Premana; Anak Agung Ngurah Krisna Dwipayana (Universitas Airlangga, 2023)
Background: Supracondylar fractures are one of the most frequent pediatric bone fractures. There are well-known treatments for this fracture. The most commonly used procedure is closed percutaneous reduction pinning, and open reduction internal fixation is for irreducible fractures. This study aims to evaluate and review those two procedures in treating a supracondylar humeral fracture in children by evaluating the clinical and functional outcomes.Methods: Systematic review and meta-analysis (PRISMA) were conducted. Using Boolean operators, literature was searched through PubMed, Google Scholar, Science Direct, and Cochrane Library. The outcomes assessed by Flynn's criteria include functional aspects, cosmetic factors, and other outcomes.Results: From 130 studies obtained, after a full-text review, four studies were included in the systematic review. The total sample size was around 268 patients with a mean age of 4-14. Male patients were higher than females. There is no significant difference in satisfactory outcomes measured by Flynn’s Criteria.Discussion: Flynn's criteria was found to be different in the result of the studies. Insignificant loss of carrying degree and Baumann's angle between two procedures. Some complications, like nerve injury, infection, and scar, were also seen after surgery.Conclusion: The two approaches have an insignificant difference in their functional outcome. The choice of which procedure to perform relies on the surgeon’s preference and the situation of the fractures.